The influence of pediatric tracheostomy on the body weight percentile of children. (December 2016) - Yankasari, Shereen; Lee, Yoon Se; Chang, Won Kyung; Moon, Hyun; Kim, Jiwon; Roh, Jong-Lyel; Choi, Seung-Ho; Kim, Sang Yoon; Nam, Soon Yuhl
Abstract: Objectives: The purpose of this study was to evaluate the changes in body weight following tracheostomy in pediatric patients. Methods: Ninety-eight patients who underwent tracheostomy at the age of 0–6 years were enrolled. The body weight and growth percentile were measured before tracheostomy and at 1, 6, and 12 months after surgery. The body weight and growth percentile were plotted against time, which was compared with Korean growth chart curve. A Retrospective observational cohort study was performed. Results: The mean body weight increased gradually from 6.7 (±0.51) kg to 10.84 (±0.15) kg at 12 months post-surgery (p < 0.01). The growth percentile also increased from 24.41 (±3.18) to 40.6 (±4.10) during the follow-up period (p < 0.01). We analyzed the patients with a low growth percentile (≤50th percentile). In these patients, the mean body weight increased from 4.92 (±0.27) kg to 8.97 (±0.27) kg and the growth percentile also increased from 11.02 (±1.32) to 30.56 (±3.31) (all p < 0.01). Ventilator-independent patients also presented similar pattern of body weight and its percentile. Conclusions: Body weight increased after tracheostomy that was safely performed in children requiring airway management.